Analysis of Accident Investigation Techniques at The Location of The Ore Hauling Road Location (ICAM Analysis Method) - Hermei wahyu Cahyadi; Wartini Wartini; Nur Ani (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
ICAM (Incident Cause Analysis method) is one of the investigation techniques used to analyze accidents and PT XYZ uses ICAM (Incident Cause Analysis method). Based on accident data for the last 3 years at PT XYZ, there has been a significant increase in the number of accidents caused by work activities, namely in 2022-2023 an increase of 5 cases (2.7%) and 2023-2024 an increase of 4 cases (2.08%). The purpose of this study is to analyze the effectiveness of the Incident Cause Analysis Method (ICAM) method in investigating accidents at the location of the ore haul road at PT XYZ in 2023.This research uses qualitative descriptive with a case study approach. The research population was 8 cases. Subject research cases of accidents on ore hauling roads. The object of the research is the occurrence of accidents in the period of 2023. Secondary data sources from investigation reports. The results of the findings of this study highlight that there is an absence or failed defence 22% (DF04-Awareness-Supervision 37.5%), individual/team factors 20% (IT12-Errors or violations of work methods 37.5%), Human-Environmental Factors 17% (HF05-situational awareness 37.5%), Workplace environment 19% (TE05-Normal operating situations and TE12-routine/non-routine tasks 25%), Organizational Factors 22% (OR-Organization 62.5%). Research conclusions from 8 cases of accidents caused by factors Absent or failed defence (22%) and organizational factors (22%). company suggestions are required to fulfil field supervision competencies, companies make, implement and review work operational standards (SOPs), companies are required to repair roads or reduce road grades to make them safer, selective in labour selection, install signs in dangerous areas, evaluate SOPs, JSA and HIRA regularly and conduct training to all workers, supervisors are required to conduct coaching to workers who are their responsibility. Keywords: Accident Investigation, ICAM Data Collection, ICAM Analysis, Occupational Health and Safety